2017
DOI: 10.1111/ijd.13701
|View full text |Cite
|
Sign up to set email alerts
|

Teaching & Learning Tips 5: Making lectures more “active”

Abstract: Challenge: Although lecturing is an efficient method for the dissemination of information, it has long been criticized for learner passivity and diminished knowledge retention. Active learning strategies to engage the audience in the learning process can facilitate a bidirectional flow of ideas and content between teacher and students during a lecture to keep learners engaged and participating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 21 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…Consequently, this will reduce students' levels of anxiety, improve the active learning process and promote life-long learning. 8 Many teachers have reported that students who are taught using ARS technology are confident and enthusiastic learners.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, this will reduce students' levels of anxiety, improve the active learning process and promote life-long learning. 8 Many teachers have reported that students who are taught using ARS technology are confident and enthusiastic learners.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 One way to achieve student-focused learning is to get students actively engaged in classrooms. 7,8 Medical educators are always looking for new approaches for teaching to ensure that learning is achieved. 6 One way to achieve this is by applying student-centred interactive teaching.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Doctors are a part of the large community of WeChat users, and many researchers have noted this phenomenon. Medical education by social media has been accepted by doctors around the world [5,[17][18][19]. In recent years, an increasing number of studies on emerging social media in the medical field, from mobile phone texts to Twitter, Facebook, and microblogs, have been reported [20][21][22].…”
Section: Introductionmentioning
confidence: 99%